The generation of passive dual wavelengths Q-switched YDFL by MoSe2film - Ahmad, Harith; Rashid, F.A.A.; Azzuhri, Saaidal Razalli; Salim, M.A.M.; Shaharuddin, R.A.; Ismail, M.A.; Razak, M.Z.A. (John Wiley & Sons, 2016)
A simple ytterbium doped fiber laser (YDFL) setup was used to generate Q-switching pulses by using a D-shaped polished fiber as a wavelength selective filter. The gain medium used in the cavity was ytterbium doped fiber with length 70 cm. By utilizing a MoSe2 film as saturable absorber into the cavity, a stable dual wavelength was produced at 1036.69 and 1039.22 nm. The wavelength separation of the output spectrum was 2.53 nm. We found a maximum pulse energy of 0.99 nJ and shortest pulse width of 1.2 μs. We have determined consistent dual-wavelength Q-switching pulses for the 1-micron region.